Metabolic and respiratory effects of theophylline in the preterm infant. Issue 1 (1st July 2000) - Carnielli, Virgilio P; Verlato, Giovanna; Benini, Franca; Rossi, Katia; Cavedagni, Monica; Filippone, Marco; Baraldi, Eugenio; Zacchello, Franco
Abstract : BACKGROUND: Methylxanthines are often administered to preterm infants for the treatment of apnoea. AIMS: To study the effects of theophylline on energy metabolism, physical activity, and lung mechanics in preterm infants. METHODS: Indirect calorimetry was performed for six hours before and after administration of a bolus of theophylline (5 mg/kg) in 18 preterm infants while physical activity was recorded with a video camera. Lung mechanics measurements were performed at baseline and 12 and 24 hours after theophylline treatment. RESULTS: Theophylline increased mean (SEM) energy expenditure by 15 (5) kJ/kg/day and augmented carbohydrate utilisation from 6.8 to 8.0 g/kg/day, but fat oxidation was unchanged. After theophylline treatment, preterm infants had faster respiration, lower transcutaneous CO2, and improved static respiratory compliance without increased physical activity. CONCLUSIONS: A bolus of 5 mg/kg theophylline increased energy expenditure independently of physical activity, increased carbohydrate utilisation, and improved respiratory compliance. The increased energy expenditure could be detrimental to the growth of the preterm infant.